Threshold magnetoresistance in anistropic magnetic 2D transition metal dichalcogenides. Issue 12 (12th March 2018) - Xu, Hongjun; Hsu, Ming-Chien; Fuh, Huei-Ru; Feng, Jiafeng; Han, Xiufeng; Zhao, Yanfeng; Zhang, Duan; Wang, Xinming; Liu, Fang; Liu, Huajun; Cho, Jiung; Choi, Miri; et al.
Abstract : A large negative, threshold, and quadratic magnetoresistance of −10% is observed in VS2 . Abstract : Recently many novel magnetoresistance (MR) phenomena have been reported from studies of two dimensional (2D) materials. Here, we report on the exotic transport behavior of VS2 . A large negative and quadratic MR of −10% is observed for an in-plane magnetic fieldB up to 14 T. Remarkably, when the applied field deviates from the in-plane orientation there is a threshold field, B c, and the MR shows a plateau of near zero MR. WhenB <B c, only a single state exists and the transition between quantum spin states is forbidden. Our work sheds new light on the MR of magnetic 2D materials with localized states and may spur further investigations.